Breaching the Bronze Wall: Franks at Mamluk and Ottoman Courts and Markets - Apellániz, Francisco (Mediterranean Reconfigurations, 2020)
Breaching the Bronze Wall deals with the idea that the words of honorable Muslims constitute proof and that written documents and the words of non-Muslims are of inferior value. Thus, foreign merchants in cities such as Istanbul, Damascus or Alexandria could barely prove any claim, as neither their contracts nor their words were of any value if countered by Muslims. Francisco Apellániz explores how both groups labored to overcome the 'biases against non-Muslims' in Mamluk Egypt's and Syria's courts and markets (14th-15th c.) and how the Ottoman conquest (1517) imposed a new, orthodox view on the problem. The book slips into the Middle Eastern archive and the Ottoman , and scrutinizes sharia's intricacies and their handling by consuls, dragomans, qadis and other legal actors. Readership: Readers of Ottoman and Mamlūk history, Islamic law and justice and anyone interested in the history of Venice and the East and Christian-Muslim relations, as well as cross-cultural relations more broadly.